Becoming paradigm: the image of the Turks in the construction of Pius V’s sanctity - Giuseppe Capriotti (Il Capitale Culturale: Studies on the Value of Cultural Heritage, 2017)
This essay analyses, through three exemplary images, the way in which the image of the Turkish enemy was used to promote the beatification and sanctification of pope Pius V, progressively becoming the emblem of all the battles the Church had to fight against any form of religious and political dissidence in the modern era. While in the frontispiece published in the Vita by Girolamo Catena (1586) the victory over the Turks is remembered along with that over the Huguenot heretics, in the painting of the beatification, conceived by Lazzaro Baldi in 1672, the pope is celebrated only and exclusively as the prophet who received the revelation of Lepanto’s victory. Following the canonization (1712), Andrea Procaccini realised the altarpiece for the chapel of St. Pius V in Santa Maria Sopra Minerva in Rome, where the Turkish enemy, personified as a woman, is floored by St. Michael archangel, who is the alter ego of St. Pius V. In this case it is possible that the Turkish woman does not only represent the Ottoman Empire, but also, more generally, Heresy and the battles that the Church must lead in an increasingly secular Europe, that is becoming more and more independent from the dictates of Catholicism.